The Origin of Modern Physical Science: Some Passages from "A Theory of Wonder" - Munévar, Gonzalo (Filozoficzne Aspekty Genezy, 2022)
The triumph of the Copernican revolution is commonly associated with the introduction of the scientific method, mainly by Galileo. The nature of science presumably depends on the way observation passes judgment on theory. This is how, according to empiricism, the practice of science improves our worldviews. Some historically inclined philosophers of science, most notably Kuhn and Feyerabend, have insisted on paying attention to what Galileo actually said and did. Shockingly, he drives a dagger through the heart of empiricism: observation does not have such priority over theory, because observation itself assumes theory. This is what he argues when dismantling Aristotle’s Tower Argument, according to which a stone dropped from a tower falls straight down to the base of the tower. If this is so, the Earth cannot rotate, for it would carry the tower with it, making our observation of the stone’s flight wildly different. According to Galileo, to conclude that the stone really falls vertically requires the assumption that the Earth does not move – the theoretical issue in question. Given Galileo’s proper understanding of the nature of science, I view Feyerabend’s principle of proliferation as the realization that a good strategy for the latter is to elaborate radical alternatives and, on their basis, reconsider what counts as evidence. Moreover, a science produced by human brains should be analyzed on the basis of evolutionary theory and neuroscience. From that perspective, we may be able to defend a sensible notion of relativism. These considerations have led me to the main arguments of my new book, A Theory of Wonder: Evolution, Brain, and the Radical Nature of Science (Philosophy of Science, Vernon Press, Wilmington — Malaga 2021). I hope to entice the reader into a discussion of some of the issues developed there.